One thousand plant transcriptomes and the phylogenomics of green plants - Leebens-Mack, James H.; Große, Ivo; Porsch, Martin; Quint, Marcel; Koch, Marcus (Nature, 2019)
The One Thousand Plant Transcriptomes Initiative provides a robust phylogenomic framework for examining green plant evolution that comprises the transcriptomes and genomes of diverse species of green plants.
Das pdf enthält 20 Seiten (Text und Anhänge)
Gesehen am 16.01.2020